2019
DOI: 10.1089/acm.2018.0305
|View full text |Cite
|
Sign up to set email alerts
|

Naturopathic Medicine for the Management of Endometriosis, Dysmenorrhea, and Menorrhagia: A Content Analysis

Abstract: Objectives: To explore the recommendations of naturopathic medicine for the management of endometriosis, dysmenorrhea, and menorrhagia, drawing on traditional and contemporary sources. Design: Content analysis. Setting: Australia, Canada, and the United States of America (USA). Subjects: Contemporary sources were identified from reviewing naturopathic higher education institutions' recommended texts, while traditional sources were identified from libraries which hold collections of naturopathic sources. Source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…It was also common for selection processes to place importance on TK with greater predominance in traditional sources, such as interventions appearing frequently within or across sources, and those with consistency of use over time as proxy measures for safety and potential efficacy (Alizadeh et al, 2017; Bae et al, 2019; Birch & Sherman, 1999; Buentzel et al, 2020; Chen et al, 2015, 2020; Connelly et al, 2020; De Vos, 2010; Flatt, 2016; Guo‐Jing et al, 2020; Han et al, 2017; Lardos et al, 2011; May et al, 2014; Sahranavard et al, 2014; Steel & Adams, 2011c; Thomas, 2011; Xia et al, 2020; Zhang et al, 2014). The perceived authority, authenticity and influential impact of the source on its tradition were also given importance during selection of TK in research and practice (; Adams et al, 2011; Adams, Schneider, et al, 2012; Alizadeh et al, 2017; Bae et al, 2019; Connelly et al, 2020; De Vos, 2010; Flatt, 2016; Jaric et al, 2014; May et al, 2012; Petran et al, 2020; Reid et al, 2018; Yang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It was also common for selection processes to place importance on TK with greater predominance in traditional sources, such as interventions appearing frequently within or across sources, and those with consistency of use over time as proxy measures for safety and potential efficacy (Alizadeh et al, 2017; Bae et al, 2019; Birch & Sherman, 1999; Buentzel et al, 2020; Chen et al, 2015, 2020; Connelly et al, 2020; De Vos, 2010; Flatt, 2016; Guo‐Jing et al, 2020; Han et al, 2017; Lardos et al, 2011; May et al, 2014; Sahranavard et al, 2014; Steel & Adams, 2011c; Thomas, 2011; Xia et al, 2020; Zhang et al, 2014). The perceived authority, authenticity and influential impact of the source on its tradition were also given importance during selection of TK in research and practice (; Adams et al, 2011; Adams, Schneider, et al, 2012; Alizadeh et al, 2017; Bae et al, 2019; Connelly et al, 2020; De Vos, 2010; Flatt, 2016; Jaric et al, 2014; May et al, 2012; Petran et al, 2020; Reid et al, 2018; Yang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Gui Zhi Fu Ling Wan is the most common Traditional Chinese herbal medicine prescription used in the treatment of endometriosis 23 and includes ingredients commonly recommended by naturopaths and western herbalists. 24 However, the evidence of effectiveness for herbal medicine is limited. Systematic reviews of studies investigating Chinese herbal medicine for endometriosis have been inconclusive due to a lack of high-quality trials 25 and a previous study using raw herbs made into a decoction had issues with nding an inert placebo.…”
Section: Discussionmentioning
confidence: 99%
“…57 Hydrotherapy and heat therapy have been proposed as beneficial in pain reduction in cases of PD. 58 With regards to hydrotherapy, warm baths and hip/sitz baths have been speculated as therapeutic for painful menses, while Heat patches containing iron chips have also been suggested to provide relief of PD discomfort equal to ibuprofen. 59 Nevertheless, a recent systematic review and metanalysis revealed only little-to-moderate pain reduction in heat therapy.…”
Section: Less-explored Approaches On the Management Of Pdmentioning
confidence: 99%